Neck-cooling improves repeated sprint performance in the heat - Sunderland, Caroline; Stevens, Ryan; Everson, Bethan; Tyler, Christopher J. (Frontiers in Physiology, 2015)
The present study evaluated the effect of neck-cooling during exercise on repeated sprint ability in a hot environment. Seven team-sport playing males completed two experimental trials involving repeated sprint exercise (5 x 6 s) before and after two 45 min bouts of a football specific intermittent treadmill protocol in the heat (33.0  0.2 ºC; 53 ± 2% relative humidity). Participants wore a neck-cooling collar in one of the trials (CC). Mean power output and peak power output declined over time in both trials but were higher in CC (540 ± 99 v 507 ± 122W, d = 0.32; 719 ± 158 v 680 ± 182 W, d = 0.24 respectively). The improved power output was particularly pronounced (d = 0.51 – 0.88) after the 2nd 45 min bout but the CC had no effect on % fatigue. The collar lowered neck temperature and the thermal sensation of the neck (P < 0.001) but had no effect on heart rate, fluid loss, fluid consumption, lactate, glucose, plasma volume change, cortisol or thermal sensation (P > 0.05). There were no trial differences but interaction effects were demonstrated for prolactin concentration and rating of perceived exertion (RPE). Prolactin concentration was initially higher in the collar cold trial and then was lower from 45 minutes onwards (interaction trial x time P=0.04). RPE was lower during the football intermittent treadmill protocol in the collar cold trial (interaction trial x time P = 0.01). Neck-cooling during exercise improves repeated sprint performance in a hot environment without altering physiological or neuroendocrinological responses. RPE is reduced and may partially explain the performance improvement.